Formative research to address vaccine hesitancy in Tajikistan. Issue 10 (5th March 2021) - Klassen, Ann Carroll; Milliron, Brandy-Joe; Reynolds, Leslie; Bakhtibekova, Zubayda; Mamadraimov, Suhaily; Bahruddinov, Mutribjon; Shokamolova, Sitora; Shuster, Michelle; Mukhtar, Sarah; Gafurova, Maftuna; Iskandari, Malika; Majidian, Rauf; et al.
Abstract: Introduction: Incomplete childhood vaccination is associated with caregiver vaccine hesitancy, conceptualized by "3 Cs": high complacency, low confidence, and low convenience. To expand on existing evidence drawn primarily from the Americas and Europe, and develop culturally appropriate interventions, this research explored drivers of vaccine hesitancy in the Central Asian country of Tajikistan. Methods: In twelve diverse districts, clinic-based immunization record abstraction identified purposive samples of children who were up-to-date (N = 300) or not (N = 300) on all first year vaccines. Using a modified case-control design, the structured face-to-face in-home survey of 600 caregivers compared knowledge, attitudes and practices regarding childhood vaccination by up-to-date status. Socio-demographic and psychological factors associated with hesitancy were identified, using a 22-item vaccine hesitancy scale, with subscales measuring complacency, confidence, and convenience. Overall contribution of vaccine hesitancy to up-to-date status was modeled, adjusting for other significant covariates. Results: Caregivers of not up-to-date children were more likely to report their child's health as poor, and report many logistical barriers to vaccination. Knowledge of vaccine-preventable illnesses was low, and complacency regarding vaccination was high among not up-to-date caregivers. In final multivariable models of predisposing, enabling and reinforcing influences on vaccination status, urban children, those with transportation and employed mothers were more likely to be up-to-date, while not up-to-date children included those born at home, seen as having fair or poor health, or reportedly told by clinicians to avoid immunization. Reinforcing factors included having a "vaccine passport", receiving useful information from medical providers, and believing that vaccine-preventable illnesses are serious and that most in their community are vaccinated. Additionally, vaccine hesitancy was negatively associated with up-to-date status (odds ratio 0.15, 95% C.I. 0.08, 0.26). Conclusions: Results confirm that in this traditional culture, there is a strong need for tailored communication campaigns to address vaccine hesitancy, while continuing to address systems-level barriers.